Characteristics of Wild Edible Mushroom Knowledge of Mushroom Foragers in Indonesia - Saipul Sihotang; Rudy Hermawan; Ivan Permana Putra (Jurnal Ilmu Pertanian Indonesia, 2025)
Edible wild mushrooms (EWM) are food sources which have high nutritional value. Although they are not the main choice of daily foods in Indonesia, various local communities and mushroom foragers have been consuming EWM for decades, yet without proper documentation. This study aimed to preserve the knowledge of EWM consumption to increase the popularity and public awareness of EWM as alternative food in Indonesia. Data was collected via a structural survey to 50 mushroom hobbyists with range of 18-50 years old and representing several ethnic groups in Indonesia: Javanese, Malay, Sundanese, Banten, and Bugis. Most of the respondents have consumed EWM for more than 5 years, with a frequency of consuming more than once per month, and the knowledge of foraging was obtained from their families. The edible mushrooms were collected mostly after every January and usually consumed by themselves. The location for mushroom seeking and species of EWM mostly were the forests around residence area and Termitomyces spp. (local names: ‘jamur barat’, ‘jamur bulan’, ‘jamur rayap’, ‘jamur trucuk’, ‘jamur sempagi’, respectively). The taste of mushroom was the main reason for forage activity among the hobbyists. They generally consumed all parts of basidiomata and preferred the soft texture of fruiting body. The soup dish was the most preferred by foragers, in contrast to fried cooking type. Most of them distinguish EWM from poisonous mushrooms by observing certain structures basidiomata, however, cases of wild mushroom poisoning have occurred among foragers with low occurrence of frequency. Keywords: Indonesia; edible wild mushrooms; characteristics; mushroom foragers